2020
DOI: 10.2147/rmhp.s270326
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Nomogram for Prediction of Postoperative Pneumonia Risk in Elderly Hip Fracture Patients</p>

Abstract: Purpose Pneumonia is one of the common complications of hip fracture. This study aimed to evaluate the risk factors and apply a nomogram to predict postoperative pneumonia in elderly hip fracture patients. Materials and Methods From August 2014 to October 2019, 1113 hip fracture patients who were older than 65 years and underwent surgical treatment in our hospital were subjects of this study. Univariate and multivariate Cox analyses were used to identify independent ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…Furthermore, we employed four independent prognostic features of OS, including the signature-based risk score, T stage, N stage, and AJCC stage to construct the nomogram to quantitatively estimate the 1-, 3-, and 5- year survival probabilities of SKCM patients in TCGA cohort ( Figure 7A ). In the nomogram score system, each variable was allocated a point, and then the sum of the points was calculated as the total score, and the predicted risk corresponding to the total score was the probability of survival ( 35 ). The accuracy and sensitivity of the predictions were confirmed using the calibration plot for the nomogram.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we employed four independent prognostic features of OS, including the signature-based risk score, T stage, N stage, and AJCC stage to construct the nomogram to quantitatively estimate the 1-, 3-, and 5- year survival probabilities of SKCM patients in TCGA cohort ( Figure 7A ). In the nomogram score system, each variable was allocated a point, and then the sum of the points was calculated as the total score, and the predicted risk corresponding to the total score was the probability of survival ( 35 ). The accuracy and sensitivity of the predictions were confirmed using the calibration plot for the nomogram.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of POP was 5% among 24 studies; 6 studies reported a prevalence of more than 10%. 7 , 10 - 14 In particular, one study a very high prevalence of 18%. 11 That study was conducted on patients who underwent subtrochanteric fracture surgery, a relatively high proportion of whom had lung malignancies (6.3%).…”
Section: Discussionmentioning
confidence: 99%
“… 19 Early surgery leads to early restoration of motor function and fewer of the complications associated with bed rest. 13 Six papers on surgical delay were included in our meta-analysis. One study found that a delay of more than 24 h was associated with an increased risk of POP, while two others found that a delay of more than 36 h increased the risk (although in one of these studies the association lacked statistical significance).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that perioperative pulmonary complication is related to reduced chest ventilation capacity in bedridden patients, pre-existing morbidities, and exposure to nosocomial pathogens or pneumonia following hip fracture is common. 25 The incidence of postoperative pneumonia for the general population undergoing orthopaedic surgery is 0.7% 26 and with a range of 0.45% to 14.4%. 27 Bohl et al 28 indicated that advanced age, functional dependency, increased operative time, previous COPD, and diabetes are risk factors for developing postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 99%